2019
DOI: 10.1016/j.ibror.2019.07.1722
|View full text |Cite
|
Sign up to set email alerts
|

Observation of environments with different restorative potential results in differences in eye patron movements and pupillary size

Abstract: Highlights Mean number of fixations, fixation durations and pupil dilation were calculated for high and low restorative potential scenes. There were significantly more fixations for low restorative than for high restorative scenes. Fixation times had the predicted inverse relationship, with low restorative settings having a significantly shorter time per fixation than high restorative scenes. Higher measures of pupil dilatation were rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Three studies to date have examined the associations between nature images and pupil diameter; participants viewed photographs rated either high or low in restorative value ( Nordh et al, 2010 ; Martínez-Soto et al, 2019 ; Marois et al, 2021 ). Nordh and colleagues noted that pupil size was smaller when participants viewed park photos they rated as more restorative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies to date have examined the associations between nature images and pupil diameter; participants viewed photographs rated either high or low in restorative value ( Nordh et al, 2010 ; Martínez-Soto et al, 2019 ; Marois et al, 2021 ). Nordh and colleagues noted that pupil size was smaller when participants viewed park photos they rated as more restorative.…”
Section: Introductionmentioning
confidence: 99%
“…The other two papers, in contrast, found that pupil diameter was larger when participants viewed high compared with low restorative photos. Martínez-Soto and colleagues interpreted these results within the context of the emotional valence of the photos, suggesting that a greater emotional response associated with higher restorative ratings of the photos was associated with a larger pupil size ( Martínez-Soto et al, 2019 ). Marois and colleagues suggested that the nature images with higher restoration potential, the high-mystery images, may have prompter greater engagement of attention with the natural images ( Marois et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… Valtchanov and Ellard (2015) also observed consistent results by showing a lower number of fixations, fixations of longer durations and a reduced amount of eye blinks when viewing nature scenes compared with urban scenes (see also Franěk et al, 2018 ). Moreover, Martínez-Soto et al (2019) replicated the reduced number of fixations and their longer duration for nature restorative images compared with urban non-restorative images, but also showed higher pupil dilation for restorative nature images, which they ascribed to the superior affective preference for restorative nature environments. Overall, these results support ART’s interpretation that restorative environments elicit lower engagement of voluntary attention, particularly when comparing urban and nature scenes.…”
Section: Introductionmentioning
confidence: 61%
“…The observation of higher voluntary attentional involvement for the settings containing more restoration potential (i.e., higher levels of mystery and higher fascination ratings) seem at first glance to contradict most of the eye-tracking studies focused on the deployment of visual attention during interaction with nature (Berto et al, 2008;Valtchanov and Ellard, 2015;Franěk et al, 2018;Martínez-Soto et al, 2019). In these studies, participants were typically exposed to nature and urban settings either in real or virtual form (i.e., using images), and oculometric measures were collected to infer their attention deployment toward the settings.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation